Bird : the definitive visual guide. - 4 0 16; National Audubon Society; Frances, Peter.;Burnie, David; 5 National Audubon Society.;BirdLife International (New York : DK Publishing, 2007)
This visual guide to every bird order and family profiles more than 1,500 species, photographed in their native environment by photographers around the globe. Authoritative, comprehensive, and completely up to date, this reference volume of the world's birds illustrates the full range of birds, bird behavior, and bird-watching locations organized in taxonomic order with detailed introductions to every bird order. Features special double-pages on the most spectacular birds and an audio CD of bird songs and calls.
Includes index.
Keywords: 2 -- 0; 6; Birds;Birds -- 20 -- Identification.;Pictorial works; 20; 2